DESAIN SISTEM OTOMATISASI POMPA MENGGUNAKAN PICOBOX DI PDAM KOTA DENPASAR - Dewa Gede Uki Atmaja; Cok Gede Indra Partha; I Gede Dyana Arjana (Jurnal SPEKTRUM, 2020)
One of the uses of water resources can be done through the Regional Water Company(PDAM). Equipment needed in a water supply system that uses wells as a source of waterinclude well pumps, booster pumps, and pump control systems so that the pumps can workeffectively and efficiently. The Operation and Maintenance Section is still using a manualsystem in carrying out its duties by coming to the location and immediately conducting aninspection. This study designed a pump automation system with Aplus Massenger picobox toolusing an SMS service. The pump automation system consists of a series of microcontrollers,GSM modules, RTC modules, and electric current sensors. SMS information on the value of theload current at the distribution substation is sent by the pump automation system according tothe sensor reading information and the time information set on the system. The load currentnotification system can provide an SMS warning of a disturbance of the load current at thedistribution substation. This pump automation system is carried out in the Treatment Room ofthe Water Treatment Pump Distribution Unit in the Denpasar City PDAM, with the result of anSMS reply in the form of "load current: 30-10-2019” is R = 64 Amperes, S = 63 Amperes, T = 64Amperes to receive the information about the value of the load at the distribution substation.